Conceitos no campo da psicanálise que colaboram com o entendimento do uso compulsivo de drogas - Albuquerque, Helga Ribeiro de (2020)
At the beginning of 20th century, a so-called “war on drugs” emerged and with it the ban on the use and commercialization of some substances. Among the disagreeing voices of this repressive and pathologizing stance, we had those of psychoanalysts who defended public policies for Harm Reduction, contradicting the stigmatizing and repressive policies. Psychoanalysis treats drug use, in general, as an important way for humans to experience cultural discomfort. Thus, according to its ethics, it concludes that is necessary to listen to what someone has to say, without stigmatizing him. This research aims to go through concepts and psychoanalytic authors, who favors health care to people who are compulsive users it. This is a theoretical paperwork in psychoanalysis, of bibliographic nature which focuses on the analysis of academic texts (books, articles and studies), transmitted electronically, by psychoanalyst authors. The electronic libraries SciELO (Scientific Electronic Library Online), PePSIC (Portal of Electronic journals of Psychology) and Portal of periodic journals of Capes were consulted. These searches were carried out through three types of index : 1) by keywords : Psychoanalyses; Drugs; Compulsion to repetition; Death drive; Enjoyment; 2) seeks to relate the terms psychoanalysis and drugs; 3) selection by intertextuality (Some of the authors were chosen for being inaugural and fundamental, and others for being contemporary with an important clinical discussion of the compulsive use of drugs). By reading the material, Freudian concepts were identified that have the function of basic theoretical assumptions which operate in the understanding post-Freudian psychoanalysts and proposing treatment for the compulsive use of psychoactive substance. In this manner methodologically, we first dedicate ourselves to understanding the social-political context of drug use. The dissertation begins with a brief history of the use of psychoactive substances. After the introduction, the research deals with fundamental Freudian concepts to understand the dynamics of the psychic apparatus in compulsive use (drive, narcissism, repetition, and death drive.) Next, it presents the view of some contemporary psychoanalysts in reference of the theme. In short, it is about interrogating the status of drug use, in its necessary relationship with concepts of Freudian and post-Freudian psychoanalysis. It was found that : a) Psychoanalysis has, as a differential, not to include drug use in the category o pathology itself, but to understand it as one of the answer to the social discomfort; b) in relation to studies by psychoanalyst, the main themes that emerges in the discussion about compulsive drug use are about “symptom”, “death drive” and ”repetition’s compulsion ; c) among Lacanian psychoanalysts, the concept of enjoyment core, relating it to the capitalist-consumerist-individualist society, which enhances addictions/ drug addictions. The aim of his research is to contribute with health care for those who are discriminated against as “chemical dependents” and, therefore, silenced about their unique history that favored compulsive drug use. Specifically, studding the subject from the Ethics of Psychoanalysis, the research is inserted in the context of the problematization about the subject its singular relationship with the compulsive use of psychoactive substances.